Numerical Analysis of Various Types of Flows Over NACA 4415 Airfoil (Dhaka University Journal of Science, 2024)
Because of the high-speed aircrafts, the distance to the other side of the world seems to be closer, as if it were situated just next door. Aerospace engineering has undergone a revolution thanks to research into airfoils. This research work has been focused on analyzing the aerodynamic performances of the NACA 4415 airfoil in turbulent flows while Mach numbers,  and Reynolds numbers,  have been taken into account. The chord length of  and  have been considered for this study. Computational fluid dynamics were employed to determine the lift, drag, and pitching moment forces, as well as their respective non-dimensional coefficients. As a result, maximum lift, moment forces have been found after the  angle of attacks, and stagnation areas are increasing dramatically behind the airfoil, proportion to the increments with the angle of attack. Additionally, the effects of pressure and velocity on every point of the airfoil's surface were studied through the analysis of pressure and velocity contours.Dhaka Univ. J. Sci. 72(1): 85-91, 2024 (January)